Emotions, COVID-19 related thoughts and satisfaction with life during the critical period from control to relaxation - Diao, Chunting; Tan, Huiping; Wen, Yanhui; Zhu, Ruiyue; Wu, Xiaoyue; Zhang, Shiqi; Zhao, Yongzhi; Liu, Nian; Zhou, Xuan; Hu, Zhen (Frontiers in Psychology, 2023)
In the context of declining mortality and increasing infectivity, COVID-19 infection was inevitable for the vast majority of people at some point. This study aimed to investigate the psychological well-being of the general population during China's transition period from strict control measures to relaxed policies in COVID-19 prevention and control, as well as the impact of COVID-19 related thoughts on emotion and life satisfaction during widespread infections. A sample size of 1578 participants was included in a cross-sectional study. Participants completed self-report questionnaires assessing positive and negative emotions, thoughts about COVID-19, and satisfaction with life. Demographic characteristics such as sex, age, and education level were controlled for in the analysis. Results indicated that participants who had been infected with COVID-19 (Omicron variant BA.5.2 or BF.7) reported lower positive emotions than uninfected and recovered participants. Moreover, the study found a significant relationship between COVID-19-related thoughts and emotion, as well as satisfaction with life. Positive COVID-19 related thoughts were found to mediate the relationship between negative emotions and satisfaction with life. Thus, having a positive view of COVID-19 and its response was crucial in promoting an individual's emotion, life satisfaction and well-being. This study represented the first extensive examination in China that evaluates how the COVID-19 pandemic had affected the general population during the crucial period from control to relaxation, with the number of infections rising and then declining over the course of a month.